Artificial Intelligence in Higher Education: The Power and Damage of AI-assisted Tools on Academic English Reading Skills - Chea, Phalla; Xiao, Yangtian (Journal of General Education and Humanities, 2024)
The research explores the impact of AI-assisted tools on academic English reading skills in the classroom and personalized learning among university students regarding how AI tools complement students’ assessments. To conduct this research, 24 students were divided into two groups of equal size: a control and an experimental group, which will be involved in an experimental study: one group using solely conventional methods and another group using AI-assisted tools in addition to conventional methods. The goal is to gain evidence on the effectiveness of AI-powered tools in enhancing reading comprehension, vocabulary acquisition, and critical thinking while identifying potential damage, such as overreliance on AI and ethical implications. It employed a mixed-methods approach, which involved an experimental study, survey, and semi-structured interview with students who either have or have not utilized AI for English reading learning. In the experimental research, pre-and post-tests were used to compare the differences in English academic reading scores between two groups of students. The survey was used to determine the students’ opinions on the effectiveness of AI tools, and individual semi-structured interviews were employed to obtain more detailed information. The findings posit that the involvement of AI tools in facilitating traditional teaching and learning methods has a more significant positive effect on improving academic English reading skills in educational settings, offering better convenience and effectiveness for students. However, challenges such as overreliance on AI and ethical implications were emphasized. The research provides invaluable insights into the potential benefits and challenges of evolving AI tools to enhance higher education English reading skills in educational settings.